Struktur Ajaran Dan Fungsi Pendidikan Karakter Dalam Geguritan Budi Pekerti - Wahyu Dyatmika , I Kadek (Metta : Jurnal Ilmu Multidisiplin, 2024)
Character education, when viewed from an educational perspective in Indonesia, refers to 18 noble values originating from national culture to develop the personality of the next generation (young generation). It is essential to carry out character education early to prevent the degradation of students' character and mentality due to current technological developments. The teachings of character education can be seen through learning at school and geguritan literary works. Geguritan Budi Pekerti is one of Bali Purwa's literary works containing Hindu ethical and religious values. This research aims to give the public an understanding of the teaching structure and function of character education in Geguritan Budi Pekerti. This qualitative research uses data collection methods through interviews, documentation, and literature study. The data that has been collected is analyzed using the hermeneutic data analysis method and presented using inductive deductive techniques. The results of this research are the structure of character education teachings in Geguritan Budi Pekerti (religious teachings, tolerance, honesty, social care) and the function of character education in Geguritan Budi Pekerti (religious function, ethical function, social function). By dissecting and studying directly the Geguritan Budi Pekerti text, it can be used as a reflection and guide for attitudes towards virtue and understanding of character education in Geguritan Budi Pekerti.